Happy, the littlest bunny [videorecording (DVD)] (Collectible classics., 2004)
Happy the Littlest Bunny is the littlest bunny in all of Cornwall County, and he sure does hate it. He's tired of having his older brothers, Patch and Moosey, picking on him all the time.